CONSTRAINTS TO THE DEVELOPMENT OF PROFESSIONAL PROJECT MANAGEMENT PRACTICES IN THE GHANAIAN CONSTRUCTION INDUSTRY - Ernest Kissi; Divine Kwaku Ahadzie; Edward Badu (Journal of Construction Project Management and Innovation)
Evidence of Professional Project Management Practices in the Ghanaian Construction Industry (GCI) dates back to the 1980s. However, to date not much  has been achieved in its advancement and deployment especially in an era where project management is considered as an important management philosophy in achieving project success. This paper reports on a study to determine the constraints that exist in the advancement of project management practices in the GCI. The paper adopted a two-stage data-gathering approach involving qualitative and quantitative techniques. The qualitative approach helped in identifying eighteen (18) Project Management (PM) variables that stakeholders believe are posing challenges to effective PM practices in Ghana. Out of the eighteen variables, nine supported existing literature while the remaining nine appear to be peculiar to the Ghanaian context. Subsequently, questionnaire containing the eighteen (18) variables were administered to 183 professionals who are involved in PM practices and then subjected to factor analysis. The paper highlights five (5) major underlying constraints namely: weak project management knowledge base, lack of clearly defined role for project managers, poor understanding of procurement practices, weak institutional framework and poor communication practices. The paper therefore recommends that, it is important for these underlying factors to be addressed conscientiously as they provide firm basis for advancing professional project management practices in the GCI